Genetic diversity and antibiotic resistance of Shigella spp. isolates from food products. Issue 11 (23rd September 2021) - Pakbin, Babak; Amani, Zahra; Allahyari, Samaneh; Mousavi, Shaghayegh; Mahmoudi, Razzagh; Brück, Wolfram Manuel; Peymani, Amir
Abstract: The emergence of multidrug‐resistant Shigella is a significant threat to global public health. Limited studies have investigated the incidence, antimicrobial susceptibility, and genetic diversity of Shigella isolated from food products. Conventional culture‐based, serologic, molecular, disk diffusion, PCR, and RAPD‐PCR methods were used to determine the prevalence rate, phenotypic and genotypic antibiotic resistance profile, and genetic diversity of the Shigella isolates from food samples including vegetable salad, ground meat, and raw cow's milk (405 samples). The prevalence rate of Shigella in food samples was 4.44%. The incidence of S. sonnei (3.7%) was higher than that of S. flexneri (0.74%). S. dysenteriae and S. boydii were not detected in food samples examined. Also, no Shigella were recovered from raw cow's milk. This study showed that the Shigella isolates were resistant to sulfamethoxazole/trimethoprim (83.3%), amoxicillin (66.6%), streptomycin (66.6%), tetracycline (61.1%), ampicillin (50%), amoxicillin–clavulanic acid (50%), azithromycin (50%), and chloramphenicol (50%) and completely sensitive to cefoxitin, cefepime, amikacin, and gentamicin. All Shigella isolates were multidrug‐resistant. We detected bla SHV resistance gene in all isolates; however, no isolate harbored bla TEM gene. RAPD‐PCR categorized the Shigella isolates into five main clusters. The highest antibiotic resistance was observed in the isolates of cluster R4. The finding of this study also indicated an association between antimicrobial resistance profiles and genotyping properties of the isolates. Novel food monitoring systems, including surveillance of multidrug‐resistant foodborne pathogens, especially in developing countries, are required to control the foodborne diseases. Abstract : Shigella spp. can be isolated from food samples, cause foodborne illness, and are responsible for serious outbreaks worldwide. Limited studies have investigated the incidence, antimicrobial susceptibility, and genetic diversity of Shigella spp. isolated from food products. In this study, we determined the prevalence rate, antimicrobial resistance patterns, and genetic diversity of the Shigella isolates from food samples including vegetable salad, ground meat, and raw cow's milk. We observed that all isolates were multi‐drug resistant. The findings of this study also indicated an association between antimicrobial resistance profiles and genotyping of the Shigella isolates. This is the first study that showed an association between antimicrobial resistance phenotypes and genotyping of Shigella spp. isolated from food.